2014
DOI: 10.5812/hepatmon.21184
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hepcidin mRNA Expression With Hepatocyte Iron Accumulation and Effects of Antiviral Therapy in Chronic Hepatitis C Infection

Abstract: Background:Iron overload is frequently observed in patients with chronic hepatitis C (CHC) and is associated with the increased risk of liver fibrosis and carcinogenesis. Hepcidin is a regulator of iron homeostasis and a component of innate immunity. Based on experimental studies, iron overload might be a result of low hepcidin synthesis in CHC.Objectives:The aim of this case-control study was to assess hepcidin mRNA expression in liver tissue of patients with CHC in terms of iron metabolism parameters, hemoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
(37 reference statements)
1
23
0
2
Order By: Relevance
“…Few studies have mentioned such an association, with no clear reference to viral load levels in chronic HCV patients and contradictory data concerning the relationship between HCV viraemia and hepcidin expression. 12,24,56 On the other hand, our observation hints at a putative differential regulation of hepcidin by the virus depending on its replication capacity and, in that respect, is in accordance with the hepcidin levels observed in our in vitro model.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Few studies have mentioned such an association, with no clear reference to viral load levels in chronic HCV patients and contradictory data concerning the relationship between HCV viraemia and hepcidin expression. 12,24,56 On the other hand, our observation hints at a putative differential regulation of hepcidin by the virus depending on its replication capacity and, in that respect, is in accordance with the hepcidin levels observed in our in vitro model.…”
Section: Discussionsupporting
confidence: 76%
“…We have previously showed that HCV core induces HAMP gene expression in hepatoma cells 23 and this may also apply to early HCV infection. Conversely, upon established infection, hepcidin expression dropped in our in vitro model and in patient sera, 12,13 in step with studies from chronic HCV patients with low intrahepatic HAMP mRNA 24 and decreased serum hepcidin, 12,13 and earlier in vitro RNA data. 25,26 Secreted protein expression was also increased throughout infection, albeit not as dramatically as mRNA.…”
Section: Discussionmentioning
confidence: 69%
“…Positive correlation of hepcidin expression with liver iron stores or serum iron concentration was observed and that corresponded to the physiological mechanisms of iron homeostasis regulation. [17][18][19] It could not explain causal relationship between iron overload and hepcidin inhibition in CHC. Changes in hepcidin synthesis, including lower serum levels in CHC patients compared to patients with other liver diseases, indicated rather a need to understand the role of this "iron regulator" in the context of disorders of the innate immune response in HCV infection.…”
mentioning
confidence: 99%
“…Changes in hepcidin synthesis, including lower serum levels in CHC patients compared to patients with other liver diseases, indicated rather a need to understand the role of this "iron regulator" in the context of disorders of the innate immune response in HCV infection. 19,20 This thesis partially may be explained by results of studies which reported inhibition of HCV replication caused by HAMP silencing in HCV replicon models. 21,22 On the contrary a direct antiviral activity of hepcidin against HCV replication in cell culture was also proved.…”
mentioning
confidence: 99%
“…It is generally accepted that HCV alters iron metabolism by reducing the level of hepcidin. [134142434445464748] Fujita et al . [43] measured hepcidin messenger RNA (mRNA) levels in liver samples from 56 patients with HCV infection, and revealed that the expression of hepcidin is strongly correlated with serum ferritin and the degree of iron deposition in liver tissues.…”
Section: The Effect Of Hepatitis C Virus Infection On Iron Metabolismmentioning
confidence: 99%